Photocatalysts Applications and Attributes - Bahadar Khan, Sher; Akhtar, Kalsoom (IntechOpen, 2019)
This book enlightens the type, chemical structure, and application of photo-catalysts. It covers the recent developments in photo-catalysts and their applications, particularly in photo-catalytic degradation of different organic pollutants, hydrogen production, etc. It provides a concise but complete coverage and overview of photocatalysts and their recent advances for a broad audience: beginners, graduate students, and specialists in both academic and industrial sectors.